The Neotropical species of the predaceous midge genus Austrohelea Wirth & Grogan (Diptera: Ceratopogonidae) - Ronderos, Maria M.; Spinelli, Gustavo R.; Grogan, Willliam L., Jr. (Zootaxa, 2017)
Two new Neotropical species of the predaceous midge genus Austrohelea Wirth & Grogan, A. sirii n. sp. and A. spinosa n. sp., and the previously known A. shannoni (Wirth & Blanton) are described, illustrated and photomicrographs provided of male and female specimens collected from several localities in Argentine and Chilean Patagonia. The similarities and differences between the three Neotropical species are discussed, and a key is provided of the males and females of these three species. The distribution of A. shannoni is extended to the southernmost region of South America.